2018
DOI: 10.1186/s13031-018-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Armed conflict, alcohol misuse, decision-making, and intimate partner violence among women in Northeastern Uganda: a population level study

Abstract: BackgroundRelations among and interactions between exposure to armed conflict, alcohol misuse, low socioeconomic status, gender (in)equitable decision-making, and intimate partner violence (IPV) represent serious global health concerns. Our objective was to determine extent of exposure to these variables and test pathways between these indicators of interest.MethodsWe surveyed 605 women aged 13 to 49 who were randomly selected via multistage sampling across three districts in Northeastern Uganda in 2016. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…This finding is consistent with findings of other studies [2,6,15,27]. This might be attributed to factors such as socioeconomic class, women's disempowerment, community acceptance for wife beating and the type of community in which the study was conducted [4,6,27,29,108,109].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with findings of other studies [2,6,15,27]. This might be attributed to factors such as socioeconomic class, women's disempowerment, community acceptance for wife beating and the type of community in which the study was conducted [4,6,27,29,108,109].…”
Section: Discussionsupporting
confidence: 92%
“…The sub region analyses found that Eastern Africa (42%) including Ethiopia and Uganda were the most affected by all forms of IPV [29,47], followed by Western Africa (41.7%). In line with our findings, the two regions that experienced high prevalence rates of IPV in comparison to other African regions [7,25] was also consistent with other studies conducted in SSA countries [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we examine an accumulating international body of knowledge, which indicates that FV is more prevalent during and often beyond pandemics, conflicts, and disasters (eg, see Guruge et al, 2017;Kelly, Colantuoni, Robinson, & Decker, 2018;Mootz et al, 2018;Parkinson & Zara, 2013;Peterman et al, 2020;Rao, 2020). In terms of explanatory pathways, Peterman and colleagues identified nine pathways linked to increased VAW/C during pandemics.…”
Section: Violence Against Women and Children (Vaw/c) During Pandemicsmentioning
confidence: 99%